PARIAMAN DALAM FOTOGRAFI EKSPRESI: ‘RUANG-RUANG’ YANG DITINGGALKAN - Mufti Fidinillah (Specta: Journal of Photography, Arts, and Media, 2020)
Pariaman In Expressions Photography: The Abandoned Spaces. Personal view of the space in this case is the city of Pariaman became the subject of the creation. Expressions photography used as a method to formulate this views through contemplation-idealization, planning, execution, consultation, editing / formation, to presentation. Topographic Photography is used as an approach to record what is visible on the surface. The abandoned in this city, such as houses, objects, and the others that found along the way become objects to tell views of this city. The series of photographs produced in this creation offers a personal view of a space that is narrated through the existing reality.   ABSTRAKPandangan personal mengenai ruang yang dalam hal ini adalah Kota Pariaman menjadi bahasan pokok dalam penciptaan ini. Fotografi ekspresi dijadikan sebagai metode untuk merumuskan pandangan tersebut dengan metode penciptaan bertahap seperti kontemplasi-idealisasi, perencanaan, eksekusi, konsultasi, editing/pembentukan, hingga penyajian. Topographic Photography dijadikan sebagai pendekatan untuk merekam apa yang terlihat di permukaan. Ruang-ruang yang ditinggalkan di kota ini, seperti rumah-rumah, benda yang ditemui sepanjang jalan menjadi objek untuk menceritakan pandangan terhadap kota ini. Rangkaian karya foto yang dihasilkan dalam penciptaan ini menawarkan pandangan personal terhadap suatu ruang yang dibahasakan melalui realitas yang ada.